(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The service sector has an exceptional role in public life. The problem is in the targeted forms of development in this area. The importance of the "humanistic heart", formed on the general basis of national ideology of social conditions of cultural heritage of social and humanistic values, has been scientifically justified by the necessity of realization of the purpose for organization and management of service field.